INFLUENCE OF CYTOKININS AND SUCROSE CONCENTRATIONS ON BULBLET CHARACTERS OF IN VITRO HIPPEASTRUM HYBRIDUM - & Salman, Al-Amery (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The First Part of this study was conducted at the Plant Tissue Culture Lab at the College of Science, University of Nahrain from October 2014 to February,2015. and completed at the Plant Tissue Culture Lab at the College of Agriculture, University of Baghdad From February 2015 to September 2015. Examine the possibility of using the tissue culture technique in the propagation of Hippeastrum hybridum.plantlets were resulted from leaves induced plant lets moved to new MS media supplemented with BA and Kin at 2.0, 1.0, 0.5, 0.0 mg.liter-1 individually or in combination and with or without NAA at 0.5, 0.3, 0.1, 0.0 mg.liter-1 to enhance shoot proliferation. Transferred shoot from the best proliferation- enhance to stage bulbs formation, MS media supplemented with BA at 6.0, 3.0, 1.5, 0.0 0 mg.liter-1 in addition to sucrose at 90, 60, 300 g.liter-1 with the present of NAA at 0.1 mg.liter-1 to increase bulbs formation, weight, and diameter .Result showed that the best shoot proliferation media was MS supplemented with 1.0 mg.liter-1 BA and 0.3 mg.liter-1 NAA which resulted in 8.30 shoots.plant-1. As for bulbs formation, the results exhibited that MS media supplemented with 6.0 mg.liter-1 BA and 90 g.liter-1 sucrose with the existence of 0.10 mg.liter-1 NAA gave the highest bulbs formation percentage, diameter, and both fresh and dry weight which were 3 bulbs.explant-1, 0.98 cm, and 1.04 and 0.25 g, respectively.